Generation of two‐dimensional electron gas to normally depleted AlGaN/GaN hetero‐interface by SiO2 deposition and subsequent high‐temperature annealing. Issue 17 (25th May 2021) - Nanjo, T.; Koyama, H.; Imazawa, T.; Kiyoi, A.; Imai, A.; Hayashida, T.; Watahiki, T.; Yamamoto, Y.; Miura, N.
Abstract: SiO2 film deposition and subsequent high‐temperature annealing resulted in the generation of a two‐dimensional electron gas (2DEG) at Al(Ga)N/GaN hetero‐interfaces, of which the 2DEG was originally fully depleted. The obtained mobilities and sheet carrier concentrations were over 1100 cm 2 /Vs and 3.0 × 10 12  cm –2, respectively. Surface energy lowering, which is proof of the generated 2DEG, was observed by electron state analysis using hard X‐ray photoelectron spectroscopy. This damage‐less method that selectively generates a 2DEG can contribute not only toward improving some characteristics in existing devices but also toward creating entirely novel devices.